Trajectories of Language and Culture of Gopali Community in Chitlang Valley - Gautam, Bhim Lal; Giri, Madhu (Glottodidactica, 2024)
Language pedagogy primarily casts light on cultural trajectories of language use in certain communities. By examining these of the Gopali community in the Chitlang Valley, located 28 miles southwest of Kathmandu, this preliminary study delves into various applied aspects of language use in the area. Preliminary observations indicate that the Gopali, a subset of the Newar ethnic group, have a distinctive linguistic and cultural identity in Nepal. However, they have yet to be recognized as a separate ethnic community despite their unique language, marital exchange, origin stories, and cultural practices. Currently subsumed under the Newar subset, the Gopali language is on the brink of extinction primarily because of an increasing level of influence exerted by Nepali, Tamang and Kathmandu-based Newar accents on Gopali speakers. As the misrecognition of language and culture was historically linked with the political-economic access of the community, we observed the impact of the political economy on the Gopali of Chitlang. This paper has been developed on the basis of data elicited from various narratives, key informant interviews (KII), life histories, language surveys, and observations conducted in October, 2021. Thus, the interpretation has been made in relation to various political, social and economic relations of language use and cultural changes. In consideration of multilingualism as a norm of language education, this study has also explored the impact of multilingualism among the younger generation in the Chitlang Valley. The study can help policymakers introduce mother tongue-based multilingual education (MTB-MLE) to children in the Gopali community.